EVALUATION OF EXCISIONAL AND INCISIONAL WOUND HEALING ACTIVITY OF ELECTROHOMEOPATHIC DRUG (SPAGYRIC ESSENCE) GREEN ELECTRICITY IN RATS - SABAT, PRASANT KUMAR; PRADHAN, SWETA PRIYADARSINI; PATRO, RANDEEP (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: The current research is an attempt to evaluate the wound healing activity of Electrohomeopathic drug Green electricity (GE) in Wistar rats. No data have been reported till date on the wound healing effect of GE. Hence the present research focuses on the scientific investigation of the wound healing activity of GE in rats. Methods: Excision and incision wounds were inflicted upon albino rats. In the excision wound model, the wound contraction, Scar residue, area and time of complete epithelization were measured subsequently on day 0, 3,6,9,12,15, 18 and 21 after inflicting the wound. Wound contraction was calculated as a percentage change in the initial wound size. In the incision wound model, the tensile strength was measured on the 10th post wounding day. Results: It was noted that the effect produced by the GE Showed significant wound healing (p<0.01) in all wound models when compared to the control group. In the case of the excision model, GE statistically increases the wound contraction rate and in the case of the incision model GE showed high tensile strength as compared to the control group. In both cases the epithelization period was significantly decreased as compared to control. Almost 100% wound protection was achieved by GE in 21 d as compared to control. Conclusion: GE (ointment) showed significant wound healing activity (p<0.01) in both the excised wound model and incision wound model in rats.